Respuesta :

Answer:

2√13 i

Step-by-step explanation:

√ (-52)

= √ [(-1) · (4) · (13)]

= √(-1) · √(4) ·√(13)

= i  · 2 · √(13)

= 2√13 i

Answer:

Step-by-step explanation:

What is the negative square root of 52?

Well first we need to write this out.

[tex]-\sqrt{52}[/tex]

The second thing to do is figure out what [tex]\sqrt{52}[/tex] is overall.

[tex]\sqrt{52}[/tex] is 7.211102551 or just 7.21

Next, we want to times the results with the negative that was in front of the [tex]\sqrt{52}[/tex].

[tex]-\sqrt{52}[/tex]= -(7.211102551)

[tex]-\sqrt{52}[/tex] = -7.211102551